Characterization and Modelling of Biomimetic Bone Through Additive Manufacturing - Niranjan Srinivasan; Mohsen Barmouz; Bahman Azarhoushang (Journal of Manufacturing and Materials Processing)
The long-term success of bone implant scaffolds depends on numerous factors, such as their porosity, mechanical properties, and biocompatibility. These properties depend on the type of material, such as metals and their alloys or ceramics, and the procedure used to create the scaffolds. This study aims to find the biomimetic properties of aluminum 6061 (Al 6061) alloy through Digital Light Processing (DLP) and sintering. Hollow cylindrical Al 6061 samples are printed through the DLP process at 90, 110, and 130 Wt.% aluminum powder concentrations inside a photocurable resin. The ideal temperature at which the material is sintered is 550 °C for 130 and 110 Wt.% and 530 °C for 90 Wt.%. The overall pore size ranges in the Al 6061 of these three concentrations from 30 μm to 700 μm. The compression test revealed the materials’ Ultimate Tensile Strengths (UTSs) to be 1.72, 2.2, and 1.78 MPa for the 90, 110, and 130 Wt.% materials, respectively. A simulation of the Al 6061 material as linear isotropic resulted in the UTS being 2.2 MPa. This novel hybrid of the additive manufacturing method and sintering created a scaffold model with anisotropic properties closer to trabecular bone, which could be used to observe fracture progression and could be tested for implant capabilities.